The Impact of Bilinguality on Second Language Learning: A Comparison of Structure and Written Expression Test Score between Monolinguals and Bilinguals - Nurdiana Nurdiana (Journal of English Language and Culture, 2020)
This study aims to examine the impact of bilinguality on the bilinguals and monolinguals’ score of TOEFL-like structure and expression test. The subjects are the students of a private university in Jakarta majoring in management. The took the test twice, consisting of 40 items (15 items in the structure section and 25 items in the written expression). The test takers had to do the test in 25 minutes. The result shows that the bilinguals perform better than monolinguals. That means the bilinguals’ score of structure and written expression is higher than that of the monolinguals.